COVID-19 vaccination and corneal allograft rejection- a review - Allen, Natalie E.; Zhang, Jie; McGhee, Charles N. J. (Frontiers in Cellular and Infection Microbiology, 2023)
Aim To provide a comprehensive literature review on the perceived correlation between COVID-19 vaccination and corneal allograft rejection, and to characterize risk factors, time course, graft outcomes and proposed immunological basis. Methods A literature review was conducted in August 2023 using 4 electronic databases: PubMed, EMBASE, MEDLINE and Scopus. Articles were sourced using key words associated with COVID-19 vaccination and corneal graft. All articles were screened for relevance by abstract review. Duplicates and articles related to COVID-19 infection were excluded. No time limits were set. Additional literature searches regarding cause of corneal graft rejection, rates of graft rejection associated with other vaccines and the cellular mechanism of rejection were also performed. Results 262 articles were identified from the literature search. 37 papers were included in the analysis based on defined inclusion criteria. This consisted of systematic reviews (n=6), review articles (n=5), retrospective studies (n=3), case series (n=8), letter to the editor (n=1) and case reports (n= 14). The majority of reported allograft rejections were in penetrating keratoplasties. Risk factors for COVID-19 vaccination associated rejection were previous allograft rejection episodes, repeat grafts and penetrating keratoplasty. Most reported rejection episodes were mild and resolved with treatment. Notably, several studies reported nil increase in corneal allograft rejection episodes over the COVID-19 vaccination period. Rejection episodes are associated with a broad spectrum of other vaccines and the complete pathophysiology is undetermined. Conclusion Corneal allograft rejection appears to be a rare complication of COVID-19 vaccination most frequently observed in high-risk corneal transplants. The true extent of this correlation remains controversial; however, clinician awareness of this risk is essential to its mitigation. Patient counselling around symptom monitoring following vaccination and discussion around topical steroid prophylaxis may be prudent.